2001
DOI: 10.1117/12.417177
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency magnetic field probe for determination of interface levels in separation tanks

Abstract: There are many principles for interface level detection in separation tanks based on capacitance, ultra sound, microwave, nuclear radiation etc. These principles work well in many situations, in others they fail.The high frequency magnetic field principle works in most of the situations that will occur in separation tanks for crude oils for detection of the clean water level, the layers of water continuous water/oil emulsion and the oil continuous oil/water emulsion, the oil level, the thickness of the foam la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A single channel MIT system has been used to measure the water content in multi-phase flow using experimental phantom recordings. It was found that the correlation between the position of the coil and the water/oil interface could be overcome by a full tomographic system [60] (a similar conclusion has also been drawn in [61]).…”
Section: Industrial Process Tomographymentioning
confidence: 67%
“…A single channel MIT system has been used to measure the water content in multi-phase flow using experimental phantom recordings. It was found that the correlation between the position of the coil and the water/oil interface could be overcome by a full tomographic system [60] (a similar conclusion has also been drawn in [61]).…”
Section: Industrial Process Tomographymentioning
confidence: 67%
“…However, ERT sensors require direct contact with the conductive media, which is not suitable for long-term metering in oil wells, since the wax or deposits might stick to the electrodes and block the conductive path between electrodes. To avoid direct contact with the flow, Hammer et al proposed high frequency magnetic methods for two phase flow measurement [8][9][10]. Another contactless tomography modality, i.e.…”
Section: Introductionmentioning
confidence: 99%